STUDI LITERATUR: KEBERHASILAN REKRUTMEN INTERNAL (ROTASI) PADA PEGAWAI TETAP DALAM PERUSAHAAN - Aprilinda Sabrina; Sri Vina Agustina; Selma Jasmine Lubuk; Shanty Komalasari (LPPM Politeknik Pratama, 2024)
The effectiveness of recruitment and selection is a measure of a company's success which lies in its quality if the availability of a number of human resources is sufficiently qualified and professional to support it. Internal recruitment, especially interesting limitations open new insights with a variety of experiences and solutions. To avoid these unpleasant internal recruiting deficiencies, it is recommended to equip employees with development programs that allow them to be up to date with changes in the external environment. Employee rotation is one of the internal recruitment which is to reduce employee boredom, increase employee motivation in the form of new work variations, create a fresh feeling at work, increase skills and more experience for staff employees, so if an employee is absent, it is the employee's job may be replaced by another employee. By holding employee rotation, employees can improve competence according to their expertise, because of course it can affect an employee's work productivity.